Building shared supervised practice in remote education: challenges and possibilities - Zampieri, Maria Teresa [UNESP]; de Sousa, Maria do Carmo (FapUNIFESP (SciELO), 2023)
This article discusses the results of a post-doctoral research that conducted an in-depth theoretical exploration on the concept of shared supervised practice and mobilized this study for the initial and continuing education of mathematics teachers. These results stem from the possibilities and challenges that emerged during four internship disciplines of the Mathematics degree course, in the remote context. Thus, theoretical reflections on literary works that dialogue with the theme are presented. Then, we contextualize these four disciplines, taught remotely in the second half of 2020, at the Federal University of São Carlos (UFSCar), São Carlos (SP) campus. Qualitative in nature, the research uses data obtained from theoretical tasks performed by the undergraduates and from class recordings, which took place via Google Meet. During the pandemic, the mobilizations that took place in the initial and continuing education of mathematics teachers were: theoretical, through studies about concepts that support shared supervised practice and through the interlocution with critical mathematics education, which are manifested in the professor’s practice by intentionality in organizing teaching; and methodological, through the pedagogical proposals planned to be offered remotely, mobilizing undergraduates and basic education teachers to debate among themselves and to examine literature that would allow them to create tasks that would overcome the logic of the exercise paradigm.
A construção do estágio compartilhado no ensino remoto: desafios e possibilidades
Keywords: Covid-19; Critical mathematics education; Mathematics teacher education; Remote teaching of mathematics in the pandemic; Supervised practice in basic education